A study of the early signs of drug induced parkinsonism. Issue 3 (March 1993) - Arblaster, L A; Lakie, M; Mutch, W J; Semple, M
Abstract : Postural tremor was recorded from psychiatric patients who had been treated with phenothiazine or butyrophenone neuroleptic drugs. None of the patients had previously been diagnosed as having extrapyramidal dysfunction. A significant number of these patients had abnormally low tremor frequencies. Low frequency tremors are often associated with Parkinson's disease (PD) so that some of these patients may have early signs of drug induced Parkinsonism (DIP). The results indicate that DIP is not necessarily characterised by a bilateral slow frequency tremor, but may initially be similar to idiopathic PD, even though its cause and prognosis are different.